Roles of biomaterials in modulating the innate immune response in ocular therapy - Rafiei, Mehrnoosh; Chung, Jin Teng; Chau, Ying (Frontiers in Drug Delivery, 2023)
The eye is a hard-to-treat organ due to its poor regenerative capacity and susceptibility to inflammation; as a result, it has an immune privilege mechanism. In the case of ocular degenerative disorders, chronic and uncontrolled ocular inflammations could overcome this immune response and initiate, exacerbate the tissue degeneration, and ultimately lead to blindness. Recent landmark discoveries on the key roles of the ocular innate immune system in regulating acute and chronic inflammations as well as tissue fibrosis and homeostasis have shed light on the value of novel treatment interventions in modulating the ocular immune responses at the molecular, cellular, and tissue levels. This strategy can be attained by targeting therapeutics to the resident phagocytes and antigen-presenting cells, namely microglia, dendritic cells, as well as the infiltrating neutrophils, and macrophages. Biomaterials pose as foreign materials to the host and interact with innate immune cells. To leverage such intrinsic immunomodulatory properties, biomaterials such as hydrogels, nanoparticles, and implants can be used alone as a treatment or with different payloads as carriers in immune-related ocular disorders. This article discusses how physicochemical properties such as biodegradability, size, shape, and charge could affect interaction with the eye's innate immune system and therefore influence the outcome towards pro- or anti-inflammatory response. Attention about the eye’s immunological response is required for designing tolerogenic biomaterials including intraocular lenses, cellular scaffolds, therapeutic molecule depots, or carriers of gene therapies. The discussion will shed light on the potential to use biomaterials to direct immune responses toward favourable treatment outcomes.